Super-rated operational concept for increased wind turbine power with energy storage. (May 2022) - Simpson, Juliet G.; Loth, Eric
Graphical abstract: Highlights: New method of Region 3 operation proposed to increase power production. Hydraulic transmission and energy storage proposed to decouple rotor and generator. Super-rated operation has the potential to increase energy production by 23% Capacity factor may increase from 53% to 66% without increasing generator size. This system will require solving several hydraulic transmission engineering issues. Abstract: A new super-rated method of wind turbine control is proposed for operation between rated and cut-out wind speeds, in conjunction with integrated energy storage, that may allow dramatically increased power capture as well as improved energy dispatchability without increasing turbine size or generator size. In the proposed system, a hydraulic transmission is used to decouple the wind turbine rotor from the electric generator, allowing for mechanical energy storage to be integrated into the system before the generator. Rather than the conventional Region 3 control, the new super-rated Region 3 + operation allows the rotor to generate additional power above the rated power limit and store that additional power for later regeneration. In this Region 3+ operation, the limit on operation is based on rotor thrust loads (instead of rotor power) so that power can increase with increasing wind speed. A case study with the NREL 5 MW reference turbine in steady Class I winds showed that super-rated operation could increase annual power production by 23% (including hydraulic transmission storage losses), without increasing mean out-of-plane blade loads, rotor size, or generator power. In addition, this new operation for this case increases the capacity factor from 53% to 66%, which increases power levelization. However, a wide array of component design issues must be addressed (especially for the hydraulic drivetrain) to determine if this potential can be realized.